The Proterozoic basement of the Arequipa massif, southern Peru: Lithologic domains and tectonics - Torres Cabrera, Paul (2008)
The Proterozoic rocks outcrops along the southern coast of Peru, on the margin of the Pacific Ocean and extends in the Western Cordillera of the Andes, forming a major exhibition of pre-Andean rocks where tectonothermal activity has been recognized preliminarily throughout Proterozoic history; being Grenville ages (~1000-1200 Ma) well documented. There are many gaps in knowledge of the Arequipa massif, for example, in lithological and tectonic part, there are so many authors taking the massif as an undifferentiated complex. We show in this paper a new Proterozoic basement mapping supported by field works. In addition we raised a discussion of the tectonic evolution of this massif.